2013
DOI: 10.5194/hess-17-1-2013
|View full text |Cite
|
Sign up to set email alerts
|

Impact of climate change on sediment yield in the Mekong River basin: a case study of the Nam Ou basin, Lao PDR

Abstract: Abstract. This paper evaluates the impact of climate change on sediment yield in the Nam Ou basin located in northern Laos. Future climate (temperature and precipitation) from four general circulation models (GCMs) that are found to perform well in the Mekong region and a regional circulation model (PRECIS) are downscaled using a delta change approach. The Soil and Water Assessment Tool (SWAT) is used to assess future changes in sediment flux attributable to climate change. Results indicate up to 3.0 • C shift… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
113
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(121 citation statements)
references
References 71 publications
6
113
0
2
Order By: Relevance
“…It was indicated that the rise in global-average surface air temperature (SAT) has been increased with an updated trend of 0.74°±0. 18°C during 190618°C during -200518°C during (IPCC 2007, and is likely to increase by 1.8 to 4.0 o C by the end of the twenty-first century depending on various greenhouse gas emission scenarios (Shrestha et al 2013). Global warming inevitably exerts considerable impacts on human beings, the environment, and economic and social developments, and these impacts have urged the scientific and social communities to improve the understanding of the cause and consequence of the phenomenon (Jiang et al 2008;Miao et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It was indicated that the rise in global-average surface air temperature (SAT) has been increased with an updated trend of 0.74°±0. 18°C during 190618°C during -200518°C during (IPCC 2007, and is likely to increase by 1.8 to 4.0 o C by the end of the twenty-first century depending on various greenhouse gas emission scenarios (Shrestha et al 2013). Global warming inevitably exerts considerable impacts on human beings, the environment, and economic and social developments, and these impacts have urged the scientific and social communities to improve the understanding of the cause and consequence of the phenomenon (Jiang et al 2008;Miao et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have compared trends in hydrological and sediment time series to land use changes (Wang et al, 2007;Memariam et al, 2012;Gao et al, 2012). Climate projections are consistent regarding warming and the acceleration of the water cycle (IPCC, 2013), however, they remain to be defined on sediment transport where projections show a high uncertainty (Shrestha et al, 2013;Lu et al, 2013). This is in part due to the fact that climate affects many factors controlling sediment yield, such as surface moisture availability, weathering processes and rates, and the nature of riparian vegetation (Nanson et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Numerical hydrological models have been used to estimate global change impacts on the surface processes of a watershed (e.g., Caballero et al, 2007;Mango et al, 2011;Shrestha et al, 2013;Ma et al, 2014). Those models are also useful tools to deal with the uncertainties on the impacts of climate change associated with the hydrological processes (Kingston and Taylor, 2010;Xu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%